Economic Holobiont: Influence of Parasites, Microbiota and Chemosignals on Economic Behavior - Houdek, Petr (Frontiers in Behavioral Neuroscience, 2018)
The article is a perspective on utilization of microorganisms and chemosignals in studying human economic behavior. Research in biological roots of economic development has already confirmed that parasitic pressure influenced the creation and development of cultural norms and institutions. However, other effects of microorganisms on human groups and individual decision-making and behavior are heavily understudied. The perspective discusses how parasitic infections, sexually transmitted organisms, and microbiota (i.e. “human holobiont”) could causally influence risk-seeking behavior, impulsivity, social dominance, empathy, political views, and gender differences. As a case study, the parasite Toxoplasma gondii and its influence on economic preferences, personal characteristics, and human appearance are examined. I also briefly review how chemosignals influence decision-making, particularly in the social preferences domain. I mention some predictions that arise from the paradigm of economic holobiont for the economic science. The conclusion summarizes limitations of the discussed findings and the stated speculations.